Measuring technical efficiency of the organic natural and bio-dynamic farming technology system on corn production in Trento, Agusan del Sur - Villacorta, Lyan Baybay
This research study investigated the efficiency of the Organic Natural and Bio-Dynamic Farming System (ONB-FTS) as practiced in the Municipality of Trento, Agusan del Sur. It generated data and information that can be useful as guide for corn farmers in practicing ONB-FTS . It used the software WIN4DEAP and DEAP 2.1 to facilitate the measurement of input-oriented Technical Efficiency (TE) of ONB-FTS and identification of farmers of best performance and establish benchmarks to arrive at recommendation to improve efficiency of farmers by means of Data Envelopment Analysis (DEA), which is a deterministic approach. The research considered factors of production such as farm size, hours of labor, man power, and materials of organic fertilizer. The data analysis focused on determining Technical Efficiency (TE) of each Decision Making Unit (DMU) under the assumptions of Constant Returns to Scale (CRS). The Technical Efficiency scores were decomposed into Pure Technical Efficiency and Scale Efficiency Effects by assuming Variable Returns to Scale (VRS). This research has found through the sampling of 19 of the total 21 test farmers, that corn production under this technology performs at 85.6 percent Technical Efficiency confounded with 13.4 percent scale inefficiency. It concluded, by decomposing the Technical Efficiency, that 47.3 percent of farmers can improve their efficiency by increasing the scale of operation, 47.3 percent by maintaining the scale of operations, and 5.26 percent by decreasing the scale of operation.